Практичне спрямування англійської мови при підготовці майбутніх фахівців дошкільної освіти - Черничко Степан; Csernicskó István; Csernicsko Istvan; Берегсасі Аніко; Beregszászi Anikó; Aniko Beregszaszi; Чичук Антоніна; Chychuk Antonina; Csicsuk Antonina (Видавництво «Код», 2025)
Резюме. Англійська мова в наш час стала мовою міжнародного спілкування. Для формування професійно орієнтованої англомовної компетентності у майбутніх фахівців дошкільної освіти виокремлено компоненти: лінгвістичний, соціолінгвістичний, предметний, психологічний і навчально-стратегічний. В умовах сучасного навчання м’які навички на заняттях з англійської мови здобувачам вищої освіти можна прищеплювати за допомогою різноманітних методів та підходів, що розглянуто у статті. Основна мета викладачів – активно взаємодіяти з студентами, відстежувати прогрес та допомагати у разі потреби. Запропоновано сценарії змішаного навчання. Сьогодення потребує виховання педагога нової формації, який володіє не лише «hard skills», але і «soft skills», тому не можна обмежувати освітній процес підготовки майбутнього вихователя традиційними формами роботи. Для підготовки майбутніх фахівців дошкільної освіти до проведення уроків англійської мови варто застосовувати проектний метод. Запропоновано схему виконання проектів.

Abstract. English has become the language of international communication in our time. Scientists suggest that by 2050, 2 billion people on our planet will speak English, which once again confirms its relevance and demand in all areas of life. All these facts indicate that knowledge of English is an integral element of a modern successful person. When forming professionally oriented Englishlanguage competence in future preschool education specialists, it is advisable to distinguish the following components: linguistic, sociolinguistic, subject, psychological and educational-strategic. The formation of all components of the English language competence of future specialists occurs with an optimal combination of the student’s external and internal motivation. And the motivation to learn a foreign language includes an understanding of the system of incentives that encourage deeper assimilation of knowledge and improvement of language skills and abilities necessary for successful learning. These skills and abilities are necessary for the effective use of language material in the process of foreign language communication. In the conditions of modern education, soft skills in English classes can be instilled in higher education students using a variety of methods and approaches, which are discussed in the article. The main goal of teachers is to actively interact with students, monitor progress, and provide assistance when needed. Blended learning scenarios are proposed. Today, social networks are closely linked to the use of mass communication. The latter traditionally accumulate, then sort and distribute information. Of particular importance are online courses with native English speakers, which stimulate the development of correct pronunciation, learning new words, acquiring communication skills, and joint activities with other higher education students. Today, there is a need to educate a new generation of teachers who possess not only «hard skills» but also «soft skills», so the educational process of training a future teacher cannot be limited to traditional forms of work. To train future preschool education specialists to conduct English lessons, it is worth using the project method. A project implementation scheme is proposed.
Practical direction of english language in the training of future preschool education specialists
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: англійська мова; майбутні фахівці дошкільної освіти; проектний метод; м’які навички; діти дошкільного віку; англомовна компетентність